Fate of orbitons coupled to phonons - Schmidt, Kai Phillip; et al. (Physical Review B, 2007)
The key feature of an orbital wave or orbiton is a significant dispersion, which arises from exchange interactions between orbitals on distinct sites. We study the effect of a coupling between orbitons and phonons in one dimension using continuous unitary transformations. Already for intermediate values of the coupling, the orbiton band width is strongly reduced and the spectral density is dominated by an orbiton-phonon continuum. However, we find sharp features within the continuum and an orbiton-phonon antibound state above. Both show a significant dispersion and should be observable experimentally.